TEMA DAN GAYA DALAM KARYA â€œDALAM SINAR MATA MUâ€ OLEH PONIRIN AMIN - Abdul Hadi, Hamidi; Musa Kahn, Sabzali; Hamidon, Nor Azlin; Harun, Zahirah (JURNAL MELAYU SEDUNIA, 2019)
This study focuses on the print artwork "Dibawah Sinar Matamu" by Ponirin Amin. He is a Malay artist who has produced print artworks since the 1970s. His work is seen as very critical thinking, symbolic and deeply meaningful. However, despite his highly symbolic and abstract modern art style, there is very little research and in-depth information about it. This is due to most of the print works are often neglected. Printed works are often viewed as trivial documentation as in booklets and exhibition catalogs yet not followed by critical writings or scientific studies of the work itself. The aim of this research is therefore to identify, analyze and examine the fathom aspects of the theme, style and the meaning of the work. This study applies the observation method, appreciation and interview of the artists. Erwin Panofsky's iconographic analysis model was chosen as the model of appreciation for this work. The findings of the research show that the work is based on the reflection and personal experience of the artist. The works are structured analytically by adapting the symbols of culture. Visual vocabulary skills, not only create aesthetic effects but also articulate the meaning which is valued by the artist. Even though the aspects of the style are a mix of western and eastern styles but the focus of this artist regarding the theme of the work speaks about culture, spirituality, soul and the oneness of God.